2012
DOI: 10.1001/archophthalmol.2012.89
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Correlations in Bardet-Biedl Syndrome

Abstract: These phenotypic differences can help guide genetic testing and genetic counseling for patients with this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 29 publications
4
59
1
5
Order By: Relevance
“…[8,9] An age-related evolution of the phenotype is well documented in BBS, [1,6] and the younger age distribution of our cohort may have influenced this. Primary enuresis was common into late childhood and adolescence in our cohort, and likely reflects the recognised urinary concentration deficits that occur in BBS.…”
Section: The New Millenniummentioning
confidence: 81%
See 2 more Smart Citations
“…[8,9] An age-related evolution of the phenotype is well documented in BBS, [1,6] and the younger age distribution of our cohort may have influenced this. Primary enuresis was common into late childhood and adolescence in our cohort, and likely reflects the recognised urinary concentration deficits that occur in BBS.…”
Section: The New Millenniummentioning
confidence: 81%
“…In the remaining 22 families testing negative for this single mutation, 3 coloured patients have subsequently had causative mutations in other BBS genes identified: 1 with compound heterozygosity in BBS 2 and 2 brothers heterozygous for novel BBS 10 mutations predicted to be disease causing. [6] From the limited information available, a number of patients testing negative did not have more than one or two primary diagnostic criteria, suggesting that the diagnosis may be uncertain. Ethnicity was not documented for all patients, but where available, confirmed that all further positive analyses were found in patients of indigenous black SA descent, with white and coloured patients accounting for a significant number of negative analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a milder phenotype has been associated with the recurrent mutation p.M390R (BBS1) [Hjortshoj et al, 2010]. Further, in a recent study, ocular phenotype evaluation for 37 BBS patients revealed that patients with BBS1 mutations had a milder phenotype than patients with mutations in other BBS genes [Daniels et al, 2012]. Other reports suggested the association between mutations in BBS1 , BBS2 , BBS3 , and BBS4 and specific ocular phenotypes and digital malformations [Heon et al, 2005].…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…These sensational observations were defined as a 'triallelic inheritance' and became a subject of intensive studies [Katsanis et al, 2001]. Some data sets confirm increased coincidence of homozygous and heterozygous BBS gene mutations in BBS patients, while others deny this relationship [Katsanis et al, 2002;Badano et al, 2003a;Beales et al, 2003;Fauser et al, 2003;Mykytyn et al, 2003;Hichri et al, 2005;Laurier et al, 2006;Smaoui et al, 2006;Hjortshøj et al, 2010;Abu-Safieh et al, 2012;Daniels et al, 2012;Redin et al, 2012]. Furthermore, the mechanistic basis for the pathogenic impact of heterozygous mutations remains largely elusive.…”
Section: Mode Of Inheritancementioning
confidence: 99%